Comparative study between lymphocyte-monocyte ratio and platelet-lymphocyte ratio: novel markers for critical limb ischemia in peripheral arterial disease - Swamy, Varsha; Raksha, R.; Rajagopalan, S. (International Surgery Journal, 2019)
Background: Peripheral arterial occlusive disease (PAOD) is frequent and often not diagnosed in time. If treatment is not initiated early, disease progression and development of Critical limb ischemia (CLI) is one possible complication. CLI is an entity with high mortality and high risk of limb amputation. As monocytes play a leading role in progression of atherosclerosis and platelets play a key role in atherosclerosis and atherothrombosis, we investigated Lymphocyte-monocyte ratio (LMR), Platelet lymphocyte ratio (PLR) and its association with CLI in peripheral arterial disease. Methods: Retrospective observational study conducted between January 2015-December 2017 including 50 patients admitted in Rajarajeswari Medical College and Hospital, Bangalore. As an optimal cut-off value, a PLR of 150 and LMR of 5 were identified. Their association with CLI noted. Results: 50 patients with critical limb ischemia, stage 3 and 4 of Fontaine classification were included in this study. 72% patients had LMR less than 5.40% patients had PLR more than 150 and 36% patients had both LMR less than 5 and PLR more than 150. 96% patients with LMR<5 and 72% patients with PLR>150 underwent amputation. Conclusions: An increased PLR and reduced LMR are significantly associated with patients at high risk for CLI. They are broadly available and cost effective. When done in early stage of the disease serves as a marker for CLI and aggressive treatment in such patients will reduce the risk of amputation.